USING INQUIRY-BASED LEARNING TO EXPLORE RESPECT OF CULTURAL BASE DESIGN: A CASE STUDY IN AMPHAWA TOURISM COMMUNITY, THAILAND - Natapon ANUSORNTHARANGKUL; Yanin RUGWONGWAN (My University, 2021)
Amphawa is a Thai valuable cultural heritage. This cultural tourism has been amplified thanks to the UNESCO award. Despite the recognition, there exists a conflict as seen obviously in the town development by cross-cultural designers. This research focuses on establishment of a proper learning model. Qualitative research was undertaken using a tool namely Ethnographic Delphi Futures Research. The results found that the method of Inquiry-Based Learning significantly made learners gain insights because of the direct interactions with the community stakeholders who truly take part in reaching the consensus which improved consistency of the design works to preserve the cultural identity.
Keywords: Delphi Method; Creativity in Education and Neuroscience